Biopesticide potential of terpenic esters enzymatically synthesized by lipases (CAL-B) immobilized on magnetic cashew apple bagasse lignin - Girão Neto, Carlos Alberto Chaves (2024)
The enzymatic biotransformation of terpenic alcohols present in Cymbopogon winterianus (citronella) essential oil enables the selective production of new compounds with improved bioactivity. This is an alternative in the production of more sustainable and biodegradable pesticides, with a greater spectrum of action and efficiency against agricultural pests. However, only a few studies have been performed using enzymatic catalysts, primarily immobilized on materials derived from natural sources. In this context, lipase B from Candida antarctica was immobilized on lignin support (extracted from cashew apple bagasse) conjugated with magnetic nanoparticles to be applied in the biotechnological synthesis of terpenic esters using either commercial alcohol or C. winterianus essential oil. Subsequently, the bioactive potential of the synthesized compounds was evaluated through antimicrobial and pesticide assays. The immobilization process took place predominantly by adsorption by interfacial activation followed by covalent bonds, and the enzymatic load of 5 mgPROTEIN/gSUPPORT was chosen, as it generated a biocatalyst (Lig-MNPs_CALB) with high catalytic activity (12.6 ± 0.7 U/g) and good immobilization yield (71.5 ± 1.2 %). Furthermore, Lig-MNPs_CALB showed great stability at 50 °C, maintaining 65 % of its activity after 96 h of exposure, and it was more stable in heptane, retaining 49.3 ± 1.3 % of its activity after 48 h. The biocatalyst obtained also showed good storage stability at 4 °C, with retention of 73 % of its activity after 60 days. For the synthesis of citronellyl butyrate ester using free and immobilized CAL-B, and synthetic alcohol as a substrate, the optimal esterification conditions were 50 °C, 1:1 molar ratio (alcohol:acid), 10 mg of either free enzyme or biocatalyst/mL of solution, and 200 RPM. The esterification yield was higher when catalyzed by the immobilized enzyme, achieving 96.4 ± 2.1 % compared to the yield obtained with free CAL-B (55 ± 3.9 %) after 24 h of reaction. The catalytic activity of Lig-MNPs_CALB was maintained after 10 reactional cycles, with a citronellyl butyrate synthesis yield exceeding 95 %, which makes this process promising to biopesticides industry. The essential oil extracted from the Cymbopogon winterianus plant was characterized and also evaluated as an alternative and low-cost source for the synthesis of terpenic esters. The major compounds present in the oil investigated were citronellal (40.32 % (v/v)), geraniol (26.77 % (v/v)), and citronellol (8.64 % (v/v)). Esterification reactions using Lig-MNPs_CALB resulted in yields of 96.1 ± 0.6 % for citronellyl butyrate and 96.9 ± 0.3 % for geranyl butyrate within 24 h of reaction, indicating that there was no enzyme inhibition due to the presence of other components. The biocatalyst also remained stable among the complex composition of the essential oil during five consecutive reaction cycles. Additionally, the antibacterial activity of citronellyl butyrate ester was superior to that of its respective alcohol for both strains of Escherichia coli and Staphylococcus aureus, with the respective ester also showing an improvement in its antifungal activity against Fusarium graminearum, decreasing its half maximal inhibitory concentration (IC50) value by 66.8 %. Furthermore, geranyl butyrate ester reduced its antifungal activity (F. graminearum) by 30.1 % compared to geraniol, and also exhibited antibacterial activity against Pseudomonas syringae pv. tomato, which adds this valuable property to its industrial applications. Lastly, the esterified C. winterianus essential oil, at the highest concentration evaluated (43372 µg/mL), decreased in 87.5 % the disease incidence and thus the disease severity of Botrytis cinerea B05.10 infection in French bean plants (Phaseolus vulgaris). Therefore, a more cost-effective approach with reduced environmental impact was developed to obtain new bioproducts with improved properties which hold the potential to be applied as biopesticides for sustainable agriculture.